SOSIALISASI PROGRAM RUMAH SUSUN SEDERHANA SEWA BAGI MASYARAKAT BERPENGHASILAN RENDAH DI KOTA PEKANBARU (STUDI KASUS RUSUNAWA REJOSARI) - Umil Khairiah; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The problem of housing and settlement is one of the problems that untilnow is still common in Indonesia, especially in large cities that have a large population and the limitations of residential land. One of the efforts to handle housing and settlement problems is to build a simple housing vertically or commonly called a rental apartment (rusunawa). However, the realization of the rusunawa program is not fully successeful as expected because of the skills and skills in socialization as well as insufficient funding support to provide facilities for socialization. The purpose of this study is to identify, describe, and analyze the socialization of Rusunawa Program conducted by UPTD Rusunawa Pekanbaru by forming a technical team.This research use grand theory of Harold D. Laswell (Effendy 2005:10) which is there are five indicators on it: 1) Who ( who said), 2) Say What (what message to say), 3.) In Which Channel (the media), 4) The Whom (to whom is’s addressed), 5) With What Effect (effect/impact).After research, it’s found that the socialization who is done by the technical team is considered still not optimal. Because after the socialization of many people who don’t know about Rusunawa Program, the information is not up to that, affect the success of socialization of Rusunawa Program for low income communities in Kota Pekanbaru.Keywords: Socialization, Rusunawa, Program